Observing past teaching activities as a trigger to the reflection of one`s own practice - Silva, Marimar da; Greggio, Saionara; Denardi, Didiê Ana Ceni; Gil, Gloria (BELT - Brazilian English Language Teaching Journal, 2010)
The present study, qualitative interpretive in nature in the area of teacher education, aims at showing the preliminary results of a project of collective reflection conducted with public school English teachers who participate in a continuing education program. More specifically, it shows the results of the analysis of the different levels of reflection identified in the collective reflection of the participants. Data from one out of ten meetings conducted during the year of 2006 were collected and transcribed for analysis. The results suggest that the observation of the activity of teaching of the other allied to collective reflection contributed to the participant-teachers to: (1) think about their work as teachers in their teaching contexts; (2) perceive some of their pedagogical actions in practice; (3) understand a bit better why they teach the way they do, and (4) reflect critically on the impact of the institutional socio-political conditions on the process of teaching.